Empowering children through photography and drawing. Issue 1 (15th March 2022) - Terton, Uwe; Greenaway, Ruth; Elsom, Sandra; Burns, Richard
Abstract : This paper discusses two methods used to collect information about children's aspirations in My Tertiary Education Day (MyTED), a primary school-based programme in low socioeconomic status (SES) areas of Queensland, Australia. The researchers hypothesised that when children are encouraged to think positively about their future, they become aware of a wide range of choices and opportunities. Of specific interest was the capacity of primary school children to aspire to a tertiary education. To learn more about children's aspirations and how these changed by taking part in the MyTED program, photo elicitation and drawing were employed. This paper investigates the ways in which drawings (MyVoice) and photo elicitation can reveal aspirations among primary school children aged 8- to 12-years. The two methods applied helped to provide a better understanding of the students emotions, their views of present world and their dreams for the future, more effectively than relying on verbal and text-based information.